Association of the polymorphisms in the gene encoding thyroglobulin with the development and prognosis of autoimmune thyroid disease. (18th August 2017) - Mizuma, Tomoyo; Watanabe, Mikio; Inoue, Naoya; Arakawa, Yuya; Tomari, Saki; Hidaka, Yoh; Iwatani, Yoshinori
Abstract: Graves' disease (GD) and Hashimoto's disease (HD) are autoimmune thyroid diseases (AITDs), and the prognosis of AITDs is different for each patient. We examined the association of polymorphisms in the Thyroglobulin (TG) gene with the pathogenesis of AITD. We genotyped TG rs180195G/A, rs853326G/A, rs2076740C/T, rs2703013G/T, rs2958692C/T and rs733735A/G polymorphisms in 137 HD patients, 131 GD patients and 89 healthy controls and also examined the levels of TG mRNA expression and serum TG. The TG rs180195 GG genotype was more frequent in HD patients ( p  = .0277), and the proportion of CD4 + cells with high levels of TG mRNA was greater in individuals with the GG genotype than in A carriers ( p  = .0107). The TG rs2703013 TT genotype was less frequent in AITD ( p  = .0186), and serum TG levels were lower in individuals with the TT genotype than in G carriers ( p  = .0170). In the TG rs2958692 polymorphism, the T allele was more frequent in intractable GD than in GD in remission ( p  = .0055), and serum titres of anti-thyroglobulin antibody (TgAb) were lower in GD patients with the TT genotype than in C carriers ( p  = .0151). In the TG rs2076740 polymorphism, serum titres of TgAb were higher in HD patients who were T carriers than in those with the CC genotype ( p  = .0359). SNPs in the TG gene were associated with the development of HD and GD, the intractability of GD, and the levels of TG mRNA expression, serum TG, and serum TgAb.